MANAJEMEN KONFLIK DAN PENGAMBILAN KEPUTUSAN DALAM PERSPEKTIF HADIST NABI MUHAMMAD SAW - Muhammad Saupiyani; Nur Melinda; Suraijiah; Fahmi Riady; Rusdiana (PT. Hasba Edukasi Mandiri, 2026)
This study discusses conflict management and decision-making from the perspective of the hadiths of Prophet Muhammad SAW. Conflict is a common phenomenon in organizations, including Islamic educational institutions, which can reduce productivity and harmony if not managed properly. Therefore, an approach is needed that is not only managerial in nature but also based on Islamic values. This study aims to identify the concepts of conflict management and decision-making based on the hadiths of the Prophet and their implementation in organizational life and Islamic educational institutions. The research method used in this study is library research with a qualitative approach. Data were obtained from the Qur’an, hadiths, books, journals, and various scientific references related to conflict management and decision-making in Islam. The data were analyzed descriptively to understand the values contained in the hadiths related to conflict resolution and fair and wise leadership. The results of the study show that Islam offers several strategies for conflict resolution, such as negotiation, tabayyun (clarification), deliberation (musyawarah), tahkim (mediation), and ishlah (reconciliation). The hadiths of the Prophet also emphasize the importance of good communication, peace, and listening to all parties before making decisions. In addition, decision-making in the perspective of hadith must be based on the principles of justice and wisdom so that the decisions made do not lead to injustice or create new conflicts. In conclusion, conflict management and decision-making based on hadith have strong relevance in building harmonious, fair, and humane organizations. Islamic values such as honesty, deliberation, justice, and peace can serve as guidelines for leaders in creating a better organizational environment oriented toward collective welfare.